The Evaluation of Case-managed Programs Targeting Individuals at Risk of Radicalisation - Cherney, Adrian (Terrorism and political violence, 2023)
There currently exists little evidence on the effectiveness of case-managed programs targeting radicalised individuals. This paper provides results from an evaluation of two case-managed interventions implemented by police in Australia, referred to as Intervention 1 and Intervention 2. Drawing on client case note data and interviews, the paper provides quantitative and qualitative results. It examines client change using a five-point metric and details two individual case studies. Results provide data on radicalised behaviours, intervention goals and services offered to clients. Individual client progress is explored, and the overall effectiveness of both programs examined. The results show a positive relationship between client change and different measures of engagement. Limitations of the evaluation methodology and data sources are acknowledged and addressed. Lessons are highlighted relating to the assessment of client change, program evaluation and the role of interventions in supporting disengagement.